-3(n-14)=56-n

Simple and best practice solution for -3(n-14)=56-n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(n-14)=56-n equation:


Simplifying
-3(n + -14) = 56 + -1n

Reorder the terms:
-3(-14 + n) = 56 + -1n
(-14 * -3 + n * -3) = 56 + -1n
(42 + -3n) = 56 + -1n

Solving
42 + -3n = 56 + -1n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add 'n' to each side of the equation.
42 + -3n + n = 56 + -1n + n

Combine like terms: -3n + n = -2n
42 + -2n = 56 + -1n + n

Combine like terms: -1n + n = 0
42 + -2n = 56 + 0
42 + -2n = 56

Add '-42' to each side of the equation.
42 + -42 + -2n = 56 + -42

Combine like terms: 42 + -42 = 0
0 + -2n = 56 + -42
-2n = 56 + -42

Combine like terms: 56 + -42 = 14
-2n = 14

Divide each side by '-2'.
n = -7

Simplifying
n = -7

See similar equations:

| 1.00x*100=2.50 | | 2=-14x | | -(6x-5)+4x-6=-1 | | 6x+8x-21=84-7x | | -0.8x-0.6+0.2x=12-4x | | -6x+2-x=2 | | -17-2x=-39 | | 6+x-1+2=7x-5-4x | | -15z=24z+36 | | Fx-gx=z | | 28x+27= | | 2((-8)-2)+8= | | 3x(2x+20)=4x-20 | | -9n+19=-8n-14 | | 6(9z-12)=9(5z+11) | | 2x+33?5x+6= | | 100x*10000=250x | | -6+4x+6x=-66 | | 4m-20=20-16m | | y=4x^3-.5x+2 | | 8c-120=240+5c | | 7x+8+4x=-80 | | x^4-20x^3+141x^2-406x+392*x-9=0 | | T(f+9)=40 | | 5y-7y=10 | | 6x-30=60-3x | | 9r-4=44+6r | | 5(2x+-7)-3(3x-10)+4= | | (D^3-D^2-4D-2)y=0 | | 46+16y=572 | | 4x-39=90 | | -17-20=-13x+80 |

Equations solver categories